Examining the Simplified Novels (SNs) as Supplementary Materials in Light of the Teachers’ Objectives and Teaching Techniques (Universitas Negeri Semarang, 2018)
Simplified novels are believed to assist in the achievement of a number of language and non-language objectives. This paper will examine the possibility of using the simplified novels as supplementary materials with secondary school students from the teachers‘ perspectives. The study uses the interview as a tool to elicit data about the teachers‘ objectives and the techniques employed in teaching the simplified novels. Ten teachers are included in the sample: 4 females and 6 males. They all work in model secondary schools and teach the simplified novels to their students. It has been found that the main objective is to improve the students‘ reading skills with a moderate potential for supporting their oral/aural skills. Increasing students‘ motivation is viewed as an important objective, while non-language objectives have received no attention. As for the teaching techniques, loud reading is found to be dominant, with almost complete absence of silent and home reading. Discussion comes in the second place (5 teachers), while role play is used by only 3 teachers. The study recommends the use of more challenging materials as the teachers believe the simplified novels being used do not help increase their students‘ vocabulary. Moreover, the teachers‘ beliefs about loud reading and non-language objectives need reexamination.